ANALISIS POTENSI, EFEKTIFITAS, EFISIENSI, DAN KONTRIBUSI PAJAK REKLAME TERHADAP PENERIMAAN PAJAK DAERAH DI KABUPATEN MINAHASA UTARA - Korengkeng, Raymond R.; Karamoy, Herman; Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Local taxes are levied by the local government and are used to finance the implementation of local government and regional development. With the enactment of local taxes, it is expected that local governments can obtain significant financial revenue posts. As one type of local taxes, advertisement tax is considered capable of increasing the financial income of each region. The purpose of this research is to know the potential of advertisement tax, the level of effectiveness and efficiency as well as to know the contribution of advertisement tax as a source of local tax revenue in North Minahasa District. The analytical method used is descriptive.. The results show the potential of advertisement tax revenues in 2017 approximately Rp. 1,250,560,290 calculated on the basis of an analysis of realization increases. The level of advertisement tax effectiveness between 2012-2016 tends to fluctuate but shows the criteria of "very effective" in 2015 with a percentage of 118.16% and 2016 of 199.59%. The level of advertisement tax effectiveness is "very effective" because it does not cost in its implementation. While the contribution of advertisement tax 2012-2016 "very less" with a percentage of 0.5% -3.32% of local tax revenues. The collection system should be supervised and controlled to increase acceptance and re-registration of taxpayers and sanctions in order to fulfill the potential.Keyword: advertisement tax, local tax, potential, effectiveness, efficiency, contribution